Behind the Counter: Exploring Pharmacists' Stressors and Lessons Learned During the Pandemic in Ontario, Canada - Zoha Zahoor; Andrew Papadopoulos; Behdin Nowrouzi-Kia; Patty Ibrahim; Mina Tadrous; Basem Gohar (SAGE Publishing, 2023)
Background: The onset of the COVID-19 pandemic has contributed to increased stress among healthcare professionals. Among these healthcare providers are Ontario pharmacists, who are facing new and pre-existing challenges and new stressors since the pandemic. Objectives: This study aimed to understand the stressors and lessons learned by Ontario pharmacists during the pandemic through their lived experiences. Methods: In this descriptive qualitative study, we conducted semi-structured one-on-one interviews with Ontario pharmacists virtually to learn about their stressors and lessons learned during the pandemic. Interviews were transcribed verbatim, then analyzed using thematic analysis Findings: We reached data saturation after 15 interviews and identified 5 main themes: (1) Communication/miscommunication with the public and other care providers; (2) high workload due to staff shortage and low appreciation/acknowledgement; (3) mismatch in market demand and supply; (4) informational gaps pertaining to the COVID-19 pandemic along with rapid protocol changes; and (5) lessons learned to improve the future of pharmacy practice in Ontario. Discussion: Our study helped us gain a better understanding of the stressors pharmacists faced, their contributions, and the opportunities that arose due to the pandemic. Conclusion: Drawing on these experiences, this study provides recommendations to improve pharmacy practice and increase preparedness for future emergencies.